Neprilysin as a Biomarker: Challenges and Opportunities - Noemi Pavo; Suriya Prausmüller; Philipp E Bartko; Georg Goliasch; Martin Hülsmann (Cardiac Failure Review)
Neprilysin (NEP) inhibition is a successful novel therapeutic approach in heart failure with reduced ejection fraction. Assessing individual NEP status might be important for gathering insights into mechanisms of disease and optimising individualised patient care. NEP is a zinc-dependent multisubstrate-metabolising oligoendopeptidase localised in the plasma membrane with the catalytic site facing the extracellular space. Although NEP activity in vivo is predominantly tissue-based, NEP can be released into the circulation via ectodomain shedding and exosomes. Attempts to determine circulating NEP concentrations and activity have not yet resulted in convincingly coherent results relating NEP biomarkers to heart failure disease severity or outcomes. NEP is naturally expressed on neutrophils, opening up the possibility of measuring a membrane-associated form with integrity. Small studies have linked NEP expression on neutrophils with inflammatory state and initial data might indicate its role in heart failure with reduced ejection fraction. Future studies need to assess the regulation of systemic NEP activity, which is assumed to be tissue-based, and the relationship of NEP activation with disease state. The relationship between tissue NEP activity and easily accessible circulating NEP biomarkers and the impact of the latter remains to be established.